Investigating the genetic epidemiology of bovine tuberculosis between compatric and contemporaneous badgers and bovines in England - Waller, Elizabeth Sophie Louise (2024)
This project aimed to investigate the contemporaneous and compatric incidents of bTB in cattle and badgers in Northern and Southern Edge counties in England and the LRA county of Hertfordshire between 2016 and 2022.